An incomplete understanding: Clarifying some causes and consequences of the 'poor comprehender' profile - Pimperton, H (2010)
The research presented in this thesis had two overarching aims; the first, to supplement our knowledge concerning the aetiological underpinnings of poor comprehension, and the second, to investigate the impact of being a poor comprehender on behavioural and educational outcomes in the school context. A combination of standardised test batteries, novel experimental paradigms, and questionnaire measures were used to obtain data that addressed hypotheses connected to these two aims. Poor comprehenders were found to have working memory deficits, as well as more specific deficits in suppressing irrelevant information from working memory. However, these deficits were largely confined to the verbal domain, giving credence to the theory that their poor performance on working memory and suppression tasks may be driven by underlying language difficulties. Poor comprehenders did show some evidence of broader executive deficits in both the verbal and non-verbal domains, raising the possibility that there might be subgroups of poor comprehenders with distinct aetiological profiles. In terms of behavioural and educational outcomes, poor comprehenders’ deficits were found to impact selectively on these areas, producing a distinct pattern of behavioural and educational impairments. These findings highlighted the need for early identification of, and effective intervention for, poor comprehenders.